MODEL OF DIGITAL TRANSFORMATION OF THE PUBLIC ADMINISTRATION SYSTEM - Popov , M. P; Komarovskyi , V. V; Bondar , A. O (Theory and Practice of Public Administration, 2021)
The development of information technology has become a factor that led to the beginning of the digital transformation of administrative services. To transform the functions of public administration on the basis of information technology, it is proposed to use the appropriate digital model of public administration (ADPA). It is a set of specialized information platforms with feedback, each of which is used to provide administrative services, receive inquiries or conduct elections, and so on. Considering the digital transformation of the system of administrative services, first of all, it should be noted the relationship that exists between the strategy of transition to e-government and the level of development of the adopted model of public administration, which also goes through certain stages of its formation. it is attributed to certain stages of transformation of the public administration system. Each of the stages is characterized by certain functions of public administration, which can be represented by e-government services. To formalize the approach to the construction of the ADPA, the paper proposes to base it on the “standard of administrative service”. It determines the conditions, procedure, and criteria for action and decision-making, which are established for executive bodies, their subdivisions, and officials. The next step in the development of the ADPA should be the transition to the administrative regulations of a certain list of services, and then, the creation on their basis and the relevant electronic administrative regulations (EAR) services. The further development of the ADPA should be based on the evolution of the very concept of e-government, which according to the modern approach should include not only websites but also operations such as transaction, interaction, integration, mobile access to e-government services, access to information and provision of information. services. Next on the agenda should be issues such as e-democracy, e-participation, the digital transformation of government, or various combinations of the above. However, Ukraine is still in the early stages of ICT use. Therefore, a single concept for the development of e-government should be developed for the state. It should be based on the use of centralized - decentralized methods of creating architecture and implementation of the ADPA. Decentralization means that departments, regional and local authorities will be directly responsible for the establishment and operation of the relevant systems. Thus coordination and integration of these processes can be provided on the basis of the application of uniform architectural principles and methods of the description of administrative regulations and processes, standards for databases using.